FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN PEMASOK (Supplier) BERAS PADA PERUM BULOG SUB-DIVRE KOTA PAREPARE - A.Nadja, Rahmawati; R. Gayatri, Eva; Lanuhu, Nurdin; Hikmawaty, Hikmawaty (Jurnal Pendidikan Teknologi Pertanian, 2018)
This study was motivated by the reduced partners as suppliers in Perum BULOG Sub Regional Division of Parepare City, where there was a decreased number of active partners performing rice procurement contract in 2017. This study aims to describe the procedures procurement rice and knowing the factors that influence the satisfaction rice supplier. This search uses the Qualitative Descriptive method. The study concluded that the procurement procedures performed from suppliers that purchasing partners deposited rice purchases at the head of the Parepare Subdivision, by making sale and purchase contracts with partners. In addition, the partners will send the rice to the designated warehouse under an approved contract. Before receiving rice, warehouse clerk BULOG will check the feasibility of rice according to the standards established by Perum BULOG Parepare Subdivision. Rice according to the standard, received by the head of the warehouse then the payment will be made to the Bank. The factors influencing supplier satisfaction at Perum BULOG are honesty of BULOG employees in the weighing rice, Perum BULOG employees also provide mandatory information, provide information periodically, explains the working procedure and accuracy of the payment time.